Taxonomic status and geographic distribution of Bryconamericus eigenmanni Evermann & Kendall, 1906 (Characiformes: Characidae) - Miquelarena, Amalia María (1999)
Bryconamericus eigenmanni Evermann & Kendall (1906) is redescribed on the basis of additional material collected at the type locality, Rio Primero, Province of Córdoba, central Argentina. Evidence supporting the validity of B. eigenmanni based on morphometric, meristic, and osteological characters is discussed. The geographic distribution of B. eigenmanni is analyzed and the species is compared with Bryconamericus iheringi, which some authors suggested was conspecific. Bryconamericus eigenmanni can be distinguished from B. iheringi by the number of maxillary teeth, premaxilla shape, body depth, caudal peduncle length, orbital diameter, and the secondary sexual dimorphism of the pelvic fin of males. The known range of B. eigenmanni suggests that it is endemic to endorrheic drainage basins of central Argentina.